Pooled Vaccine Communication Actions to Promote Vaccination in the European Union: The Case of Italy - Valentina Possenti; Roberto Croci; Roberta Terlizzi; Annina Nobile; Luca Fucili; Marco Mirra; Stefano Lucattini; Massimiliano Di Gregorio; Anna Maria Giammarioli; Scilla Pizzarelli; Francesco Corea; Antonio Mistretta; et al. (Journal of Primary Care & Community Health)
Introduction: Under the mandate of supporting European immunisation cooperation and strategies, the specific aim of this work was about focusing on vaccine communication in order to raise awareness, increase confidence and strengthen the practice for vaccination in Italy. Methods: The four-step Plan-Do-Check-Act cycle applied through a bundle of actions: (Plan) studying national vaccination scenarios and factors underlying vaccine hesitancy by developing a reference grid; (Do) creating a web platform-based toolbox with vaccine communication tools; (Check) engaging within national stakeholders within dedicated roundtables also associated to media trainings; (Act) co-developing, or co-selecting, tools to pilot amongst identified target communities. Results: In 2021, we analysed evidence on vaccine hesitancy determinants in scientific (86%) and grey (14%) literature by applying contextual, individual, and vaccine-specific categories. A total of 42 out of 204 vaccine communication tools collected and evaluated in early 2022 referred to Italy. In mid-2022, participatory dialogue and engagement with national stakeholders, media included, addressed vaccine communication improvements in different target populations. In late 2022, co-creation/selection of vaccine communication tools and their piloting focused on specific vaccinations and communities, such as the school setting for Italy. Conclusions: To address better vaccine communication outcomes, efforts on multistakeholder collaboration, training and advocacy are needed.